First Evidence of Lysogeny in Propionibacterium freudenreichii subsp. shermanii - Hervé, C. (American Society for Microbiology, 2001)
Dairy propionic acid bacteria, particularly the species Propionibacterium freudenreichii, play a major role in the ripening of Swiss type cheese. Isometric and filamentous bacteriophages infecting P. freudenreichii have previously been isolated from cheese. In order to determine the origin of these bacteriophages, lysogeny of P. freudenreichii was determined by isometric bacteriophage type analysis. The genomic DNA of 76 strains were hybridized with the DNA of nine bacteriophages isolated from Swiss type cheeses, and the DNA of 25 strains exhibited strong hybridization. Three of these strains released bacteriophage particules following UV irradiation (254 nm) or treatment with low concentrations of mitomycin C. A prophage-cured derivative of P. freudenreichii was readily isolated and subsequently relysogenized. Lysogeny was therefore formally demonstrated in P. freudenreichii.